Peran Digital Marketing Bagi Perkembangan UMKM Rufata Di Jakarta - Yaputra, Hermanto; Kristaung, Robert; Rustam, Rinaldi (Dirkantara Indonesia, 2025)
This community service aims to assist Rufata SMEs in Jakarta in enhancing their digital marketing skills, which are expected to support business growth and expand market reach. The training involved various methods, including interactive lectures, experiential learning, continuous evaluation, and post-training mentoring. The results showed a 30% increase in sales within the first three months following the implementation of digital marketing, as well as an expansion of market reach to various cities in Indonesia through social media and e-commerce platforms. However, the challenges Rufata SMEs face include limited skilled human resources in digital marketing and relatively high costs of paid advertising. To ensure sustainability and long-term success, further support in the form of ongoing training and financial assistance is needed. With such support, Rufata SMEs can continue to optimize their digital marketing potential and remain competitive in an increasingly dynamic market.